Motherhood: A Study of Mahasweta Devi’s ‘Breast-Giver’: Exploring the subjugation of women and motherhood in Mahasweta Devi's 'Breast-Giver' (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Right from the beginning of human life on this planet, women have suffered innumerable ignominies and even have undergone indignities both at the hands of man and society. Even in advanced and developed countries like the U.S.A and England, the women have remained a neglected, exploited and suppressed human being to the extent that women were considered as a booty or even prized possession of victorious kings and princes. When Napoleon Bonaparte in the early 19th century conquered a state or a country, he got married with the daughter or queen of the defeated king. The story of the trojan women in the distant past is both revealing and illustrative of the plight of women in the ancient times. Similar is the fate of women in India where there are treated as second rate citizens and even the property of man, as their identity is defined in terms of loyalty, purity and even ‘Izzat’ of the family.